2011
DOI: 10.1093/rpd/ncr307
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of dose reference levels for nuclear medicine in Greece

Abstract: Greek Atomic Energy Commission's Department of Licensing and Inspections conducted a national survey for the establishment of nuclear medicine (NM) dose reference levels (DRLs) for adult patients, in Greece. The administered activities (AAs) (MBq) were collected from 120 NM departments (88 % of total), during on-site inspections for licensing purposes. Factors influencing the image quality were also investigated. The established national DRLs represent the AA value corresponding to the 75th percentile of the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…As shown in Table 3, there is quite a distinction between Admi nistrated Activities given by countries except in Brazil which has higher dos e in bone and thy roid scan compared with other countries. The resul ts of Administrated Activities in our studies in (Table 3) and ( Figure 5) regarding the average AA in (MBq) of different types of diagnostic examinations was compared wi th a surv ey from other countries (Vogiatzi, et al, 2011;Bomben et al, 2004;Khoury etal, 1994;Flores et al, 2006;Papadopoulos et al, 1990;Lai et al, 1995;M ettler et-al., 1986;DRL Japan, 2015). Table 4 and Figure 6 shows the range of radioisotope admi nistrated activities and the admi nistrated activity for Sudanese.…”
Section: Resultsmentioning
confidence: 94%
“…As shown in Table 3, there is quite a distinction between Admi nistrated Activities given by countries except in Brazil which has higher dos e in bone and thy roid scan compared with other countries. The resul ts of Administrated Activities in our studies in (Table 3) and ( Figure 5) regarding the average AA in (MBq) of different types of diagnostic examinations was compared wi th a surv ey from other countries (Vogiatzi, et al, 2011;Bomben et al, 2004;Khoury etal, 1994;Flores et al, 2006;Papadopoulos et al, 1990;Lai et al, 1995;M ettler et-al., 1986;DRL Japan, 2015). Table 4 and Figure 6 shows the range of radioisotope admi nistrated activities and the admi nistrated activity for Sudanese.…”
Section: Resultsmentioning
confidence: 94%
“…70 ± 10 Kg) for standard procedure necessary to obtain the optimum diagnostic information as recommended by previous study [6]. The data were collected from six nuclear medicine departments (100% of total Number of nuclear medicine Departments in Sudan).…”
Section: Methodsmentioning
confidence: 99%
“…Many countries have already established DRL for more optimized radiation protection in nuclear medicine procedures [35][36][37][38][39][40][41][42]. In Korea, the first DRL values for nuclear medicine imaging studies performed in Korea were reported by MRSRC in 2015 [2][3][4].…”
Section: Drl For Optimization Of Nuclear Medicine Procedures In Koreamentioning
confidence: 99%